Development of the "Jaga Tubuhku" Educational Board Game: A Game-Based Intervention for Sexual Abuse Prevention in Indonesian Elementary Schools - Niken Indriastuti; Murfiah Dewi Wulandari (Journal of Innovation and Research in Primary Education, 2026)
Child sexual abuse represents a critical public health concern, with Indonesian data showing escalating incidents from 10,327 cases in 2021 to 14,459 in 2024. Elementary students demonstrate limited self-protection knowledge due to insufficient age-appropriate educational interventions. This study developed and validated the "Jaga Tubuhku" educational board game to enhance elementary students' self-protection knowledge against sexual abuse.  Employing Research and Development methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study engaged 34 third-grade students at MI Muhammadiyah PK Wirogunan from September to December 2025. Data collection utilized expert validation questionnaires, teacher assessments, and pre-test/post-test instruments, analyzed through paired-samples t-test and N-Gain calculations.  Expert validation demonstrated high feasibility: subject matter experts (93.7%), media experts (90.0%), and teachers (84.1%). Implementation revealed statistically significant knowledge improvement, with mean scores increasing from 61.53% to 70.59% (t = -9.764, p < 0.001). N-Gain analysis indicated moderate effectiveness (g = 0.6441, 64.41%). All students (100%) demonstrated improved understanding of body boundaries, distinguishing safe from unsafe touch, and self-protection strategies. The "Jaga Tubuhku" board game represents a feasible, effective, and culturally appropriate intervention for sexual abuse prevention education in Indonesian elementary schools, contributing validated game-based learning materials for addressing sensitive educational topics.